Percutaneous Vacuum-Assisted Debulking of Infected and Non-Infected Left-Sided Cardiac Masses Using the AngioVac System: A Systematic Review of Published Case Reports and Case Series - Felix Bratosin; Jorgelina DeSanctis; Gordana Simeunovic (Journal of Clinical Medicine, 2026)
Background and Objectives: Left-sided intracardiac masses (infected vegetations and non-infected thrombotic/tumor lesions) are traditionally managed with surgery in many cases, but procedural risk can be prohibitive. We systematically reviewed published experience with the AngioVac system for percutaneous debulking of left-sided cardiac masses. Methods: PubMed, Scopus, and Web of Science were searched for reports through November 2025, supplemented by hand-searching of congress abstract supplements; records were screened and assessed independently by two reviewers. Adult patients undergoing AngioVac removal of infected or non-infected left-sided cardiac masses were included. The primary effectiveness endpoint was technical success (≥70% debulking without conversion to open surgery). Safety outcomes included procedure-related complications. Data were synthesized descriptively due to heterogeneous designs and reporting. Patient-level and study-level data were distinguished a priori, pooled means were weighted by the number of patients contributed by each report, and pre-specified sensitivity analyses addressed possible patient overlap between reports from the same institution and exclusion of a non-intracardiac (aortic arch) target. Results: A total of 30 studies were included (predominantly single-patient reports, 90.0%). The pooled cohort comprised 42 patients; 23/42 (54.8%) had infective endocarditis (IE) and 45.2% had non-infected masses. Mean age was 62.9 years (range 30.0–86.0); sex distribution was female 47.6%, male 42.9%, and not reported 9.5%. All 42 patients were deemed to be at a prohibitively high risk of surgery. Access was mainly transseptal (29/42, 69.0%) or transapical (8/42, 19.0%). Mass size was reported in 23/42 (54.8%), with mean 23.3 mm, median 20.0 mm, and range 11.0–57.0 mm. Technical success was achieved in 35/42 (83.3%); residual mass occurred in 6/42 (14.3%) and one patient had cardiac perforation requiring conversion to open heart surgery (1/42, 2.4%). Procedure-related complications included valvular dysfunction (paravalvular leak or progressive mitral regurgitation), cardiac perforation, and cerebral infarctions (4/42, 9.5%). There were two deaths (2/42, 4.8%) after successful debulking, one in-hospital with recurrent embolic events and septic shock, and the other 4 months after the procedure following procedure-related progressive mitral regurgitation. Complications clustered in transapical procedures (3/8, 37.5% vs. 0/29 transseptal; p = 0.007) and in fungal endocarditis (2/2; p = 0.012). New clinically apparent embolic events occurred in 2/42 (4.8%), both in patients without documented cerebral protection, the choice of which to apply in the total population was unrelated to mass size (mean 23.5 vs. 23.2 mm). Estimates were stable in sensitivity analyses (technical success 32/38, 84.2% after maximal-overlap de-duplication; 31/37, 83.8% restricted to strictly intracardiac targets). Length of stay was reported in 8/42 (19.0%) with a median of 3.5 days (range 1.0–30.0). Conclusions: In published, highly selected non-surgical candidates, left-sided AngioVac debulking achieved ≥70% mass reduction in 83% of the 42 patients, with 4.8% mortality and one patient (2.4%) converting to emergency surgery. Because the evidence consists almost entirely of single-patient reports subject to publication bias, and because technical success is operator-reported and did not preclude death, these data do not support substituting debulking for a guideline-indicated operation. The technique is best positioned as a bridge or palliative strategy, with transapical access and fungal aetiology identified as signals warranting particular caution.